Greening Jobs and Skills Labour Market Implications of Addressing Climate Change - Martinez-Fernandez, Cristina (OECD Publishing, 2010)
The impacts of climate change - and especially the subsequent mitigation and adaptation policies - on labour markets are still largely unknown despite the recent demand for knowledge production and diffusion on this topic and the increasing avalanche of reports and studies from public, private and not-for-profit organisations. The search for alternative models of growth in the midst of the financial crisis has increased interest in the "green growth paradigm" and what it means for a rich-jobs recovery. This paper discusses some of the impacts of climate change including labour market regulation, the dynamics of green growth at the level of jobs and skills development, and the local implications for mitigation and enabling green growth. Although the paper does not provide all the answers to the green enigma (green jobs will come but how?), it argues that much benefit will come from focusing efforts on skills transformation, tools and initiatives. This paper benefits from the financial support of the European Commission
Keywords: Industry and Services